TANTANGAN KEMANUSIAAN ABAD KE 21 M - Rais, M. Amien (Jurnal Bestari, 1993)
In 1970 the Rome Club cooperated with Massachussets Institute of Technology Team and Potomac Associates to publish a term paper titled "The Limits to Growth". The paper consist of the identification of main problems faced by human being on global level and what people should do in order to avoid those problems bocoming more dangerous. In accordance with The Limits to Growth, there are five trends to be global danger i.e. the increasingness of industrialization, the quickness of population growth, the wideningness of malnutritio, the decreasingness of irrenewable naturalresources, and the last but not the least is that the quality living environment become more decreasing.